Labracadabra - Nelson, Jessie; Hopkins, Karen Leigh; Melmon, Deborah (New York : Viking, 2011)
Zach always wanted a dog but Larry, the full-grown mongrel his parents choose, is not it, however, he soon discovers that there is something very special--even magical--about Larry's tail.
Kirkus Review
Kirkus Review, March 2011
3.9
K-3
K-3
Keywords: Dogs -- Juvenile fiction; Human-animal relationships -- Juvenile fiction; Magic -- Juvenile fiction; Dogs -- Fiction; Human-animal relationships -- Fiction; Magic -- Fiction; Dogs -- Fiction; Human-animal relationship -- Fiction; Magic -- Fiction